A method for improving efficiency of steel nitriding by using adsorptive material and ball milling in cooperation

CN118639168BActive Publication Date: 2026-10-27CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410713915.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2026-10-27
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

[0003]目前,现有的渗氮技术处理时间长,例如为获得0.4~0.6mm厚的渗层通常需要40小时以上,严重影响了生产效率

Benefits of technology

(1)本发明提供一种利用吸附性材料和球磨协同提高钢渗氮效率的方法,采用吸附性材料元素渗入表层+球磨的方式对需要气体渗氮的工件进行吸附性材料球磨处理,通过球磨促进基体表面增加粗糙度、形成细小裂纹,使基体表面形成缺陷,更利于吸附性材料的渗入,协同吸附性材料亲和N原子能力强的原理,加速氮元素向基体扩散的速度,同时还增大基体与气体的接触面积,从而增加表面对氮原子的吸附作用;此外,采用球磨法可使吸附性材料与基材更充分的混合,在基材中分布更加均匀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118639168B_ABST
    Figure CN118639168B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal material surface strengthening, and specifically discloses a method for improving steel nitriding efficiency by using adsorptive material and ball milling, which comprises substrate material preparation, ball milling treatment and nitriding treatment. The application adopts quenching and tempering treatment to pretreat the substrate material, uses the ball milling effect to rapidly diffuse the adsorptive material to the surface layer and subsurface layer of the substrate, fully utilizes the advantage of strong affinity of the adsorptive material to nitrogen element, accelerates the diffusion speed of nitrogen element to the substrate, and improves the nitriding efficiency. The ball milling effect is used to increase various crystal defects in the surface layer of the steel substrate, so that nitrogen atoms can more easily penetrate into the steel substrate, and the catalytic nitriding effect of the adsorptive material is superimposed, further improving the nitriding efficiency of the steel. The application can effectively improve the nitriding efficiency of the steel, significantly reduce the production cost of the steel nitriding, and improve the production efficiency of the steel nitriding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface strengthening technology of metallic materials, specifically involving a method for improving the nitriding efficiency of steel by using adsorbent materials and ball milling in synergy. Background Technology

[0002] Gas nitriding involves placing the workpiece in a sealed container, introducing flowing ammonia gas, and heating it. After holding the temperature for a period of time, the ammonia gas thermally decomposes to produce active nitrogen atoms. These nitrogen atoms adsorb onto the workpiece surface and diffuse into the surface layer, thus altering the surface chemical composition and microstructure, resulting in excellent surface properties. Therefore, it is widely used in industrial production. Nitriding is primarily suitable for steel materials.

[0003] Currently, existing nitriding technologies are time-consuming; for example, obtaining a nitrided layer of 0.4–0.6 mm thickness typically requires more than 40 hours, severely impacting production efficiency. Furthermore, the depth of the nitrided layer is usually shallow, generally in the range of 0.1–0.5 mm. This thin nitrided layer is detrimental to protecting the substrate structure, and its corrosion and wear resistance often fails to meet requirements, leading to premature scrapping of nitrided workpieces. Therefore, a convenient and rapid nitriding method is needed to address the issues of nitriding efficiency and layer thickness. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0005] In view of the problems existing in the above and / or prior art, the present invention is proposed.

[0006] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for improving the nitriding efficiency of steel by utilizing adsorbent materials and ball milling in synergy.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for improving the nitriding efficiency of steel by synergistically using adsorbent materials and ball milling, comprising the following steps: (1) Heat treatment of the base material: After quenching, the workpiece is subjected to high-temperature tempering treatment; (2) Polishing treatment: After preliminary treatment with sandpaper of 150 grit, 400 grit, 1000 grit and 2000 grit respectively, the workpiece is polished to achieve a mirror finish. (3) Ball milling treatment: put the grinding balls, adsorbent material powder and matrix material into the ball milling cylinder for ball milling treatment, take out the steel matrix, clean and dry it to obtain the ball-milled matrix material; (4) Nitriding treatment: The ball-milled matrix material is placed in a nitriding furnace for gas nitriding treatment.

[0008] Furthermore, the quenching temperature in step (1) is 940~1100℃ and the quenching time is 120~180min.

[0009] Furthermore, in step (1), the high-temperature tempering treatment is carried out by furnace cooling, and the temperature of the tempering furnace is controlled at 700-900℃.

[0010] Furthermore, the grinding balls mentioned in step (3) are 95% zirconia beads, and the specific gravity of 95% zirconia beads is 6.0 g / cm³. 3 Bulk density 3.6 g / cm³ 3 The grinding ball diameter is 3~5mm; the zirconia grinding ball is 1 / 3~1 / 2 of the grinding barrel volume.

[0011] Furthermore, the adsorbent material powder mentioned in step (3) includes materials such as Ti and C that are conducive to bonding with N atoms. The adsorbent material powder does not produce any chemical reaction with the matrix and grinding balls at both room temperature and high temperature; the amount of adsorbent material powder added is 1 / 10 of the grinding barrel volume.

[0012] Furthermore, the rotational speed of the ball mill cylinder in step (3) is 110~180 r / min.

[0013] Furthermore, the ball milling temperature in step (3) is less than 100°C. Since Ti and C (adsorbent materials) first combine with O atoms at high temperatures, and then prevent the adsorbent materials from combining with N atoms during the nitriding process, thereby reducing the combination of the substrate with N atoms, the ball milling temperature should be less than 100°C.

[0014] Preferably, the ball milling process is performed at room temperature.

[0015] Furthermore, the ball milling process in step (3) takes 160 to 280 minutes.

[0016] Furthermore, the cleaning described in step (3) includes first removing dust and other stains by washing with water and then cleaning with alcohol to achieve a clean surface.

[0017] Furthermore, the nitriding treatment temperature in step (4) is 500~620℃ and the time is 120~280min.

[0018] Furthermore, the gases used in the nitriding treatment in step (4) include nitrogen and ammonia. Ammonia is decomposed into N atoms at high temperature to act as a gas permeation catalyst, while nitrogen acts as a protective gas.

[0019] Beneficial effects of this invention: (1) This invention provides a method for improving the efficiency of steel nitriding by using adsorbent materials and ball milling in synergy. The adsorbent material is used to penetrate the surface layer and ball milling is used to treat the workpiece that needs gas nitriding. Ball milling promotes the increase of roughness and the formation of fine cracks on the substrate surface, which makes the substrate surface more susceptible to defects and facilitates the penetration of adsorbent materials. In conjunction with the principle that the adsorbent material has a strong affinity for nitrogen atoms, the diffusion rate of nitrogen elements into the substrate is accelerated. At the same time, the contact area between the substrate and the gas is increased, thereby increasing the adsorption effect of nitrogen atoms on the surface. In addition, the ball milling method can make the adsorbent material and the substrate more fully mixed and more evenly distributed in the substrate.

[0020] (2) Compared with the single ball milling gas nitriding process, the present invention has a higher nitriding efficiency. At the same time, the adsorbent material has a stronger affinity for N atoms. After the adsorbent material penetrates into the surface layer, the nitrogen potential is released from the surface layer with a higher nitrogen potential to the inner layer with a lower nitrogen potential, which increases the thickness of the nitrided layer. This method is more convenient and the required equipment is simple and easy to operate, controls production costs, and is suitable for continuous production operations. Attached Figure Description

[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 This invention relates to a method for improving steel nitriding efficiency through the synergistic use of adsorbent materials and ball milling, illustrated in the process flow diagram. Figure 2 This is a microscopic morphology image of the workpiece surface after ball milling for 160 min according to Embodiment 1 of the present invention; Figure 3 This is a microscopic morphology image of the workpiece surface after ball milling for 220 min according to Embodiment 2 of the present invention; Figure 4 This is a microscopic morphology image of the workpiece surface after ball milling for 280 min in Embodiment 3 of the present invention; Figure 5 This is a diagram of the nitrided layer structure of the workpiece after nitriding treatment in Comparative Example 1 of this invention; Figure 6 This is a diagram of the nitrided layer structure of the workpiece after nitriding treatment according to Embodiment 1 of the present invention; Figure 7This is a diagram of the nitrided layer structure of the workpiece after nitriding treatment according to Embodiment 2 of the present invention; Figure 8 This is a diagram of the nitrided layer structure of the workpiece after nitriding treatment in Embodiment 3 of the present invention; Figure 9 This is a SEM image of the workpiece surface after ball milling in Embodiment 3 of the present invention; Figure 10 This is a Fe element distribution diagram on the surface of the workpiece after ball milling in Embodiment 3 of the present invention; Figure 11 This is a Ti element distribution diagram on the surface of the workpiece after ball milling in Embodiment 3 of the present invention; Figure 12 This is a diagram of the microstructure of the workpiece after modulation treatment in Comparative Example 2 of the present invention; Figure 13 This is a diagram of the nitrided layer structure of the workpiece after nitriding treatment in Comparative Example 2 of this invention; Figure 14 This is a diagram of the microstructure of the workpiece after modulation treatment in Comparative Example 3 of the present invention; Figure 15 This is a diagram of the nitrided layer structure of the workpiece after nitriding treatment in Comparative Example 3 of this invention.

[0022] Figure 16 This is a diagram of the workpiece structure after modulation treatment according to Embodiment 1 of the present invention. Detailed Implementation

[0023] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0024] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that excludes other embodiments. All workpieces used in the embodiments of the present invention are made of 42CrMo steel.

[0026] Example 1 This embodiment provides a method for improving the nitriding efficiency of steel by synergistically utilizing adsorbent materials and ball milling. The process flow is as follows: Figure 1 As shown, the specific process steps are as follows: (1) Tempering of the base material: The workpiece is subjected to overall quenching followed by high-temperature tempering. The quenching temperature is 950℃, the quenching time is 150min, the high-temperature tempering temperature is 800℃, and the tempering method is furnace cooling. The tempering process is quenching + high-temperature tempering to ensure that the parts have a uniform structure and good comprehensive mechanical properties. Therefore, tempering must be performed before nitriding to obtain a good state of comprehensive mechanical properties in the core and high surface hardness formed by nitriding. Figure 16 The image shows the microstructure after tempering treatment. The microstructure after tempering treatment is tempered sorbite (a multiphase microstructure with fine and uniform carbide particles and small spherical carbides (including cementite) distributed in the ferrite matrix). This microstructure has good mechanical properties and prepares for the subsequent nitriding operation.

[0027] (2) Polishing treatment: After preliminary treatment with sandpaper of 150 grit, 400 grit, 1000 grit and 2000 grit respectively, the workpiece is polished to achieve a mirror effect.

[0028] (3) Ball milling treatment: A 4mm diameter 95% zirconia grinding ball, the polished workpiece, and the absorbent material (Ti powder, purchased from Shandong Hongtai Wear-Resistant Materials Co., Ltd., 200 mesh) were placed together in a ball mill cylinder and ball-milled for 160 minutes at room temperature. The ball mill cylinder speed was 160 r / min. The zirconia grinding ball occupied 1 / 3 to 1 / 2 of the grinding barrel, and the Ti powder was added to 1 / 10 of the grinding barrel volume. The workpiece was then removed, washed in water, wiped with alcohol, and dried. The resulting workpiece surface microstructure is shown below. Figure 2 As shown. After being treated with adsorbent material and ball milling, the surface of the workpiece showed many protrusions compared to the original workpiece, but overall, the sample surface was smoother.

[0029] (4) Nitriding treatment: Place the ball-milled workpiece into the nitriding furnace, seal the furnace lid, start the heating element, raise the furnace temperature to 600℃, and after the temperature rise is complete, purge with nitrogen for 30 minutes (maintaining the furnace pressure at 1.3 atm), with a flow rate of 5 m³ / min. 3 / h, exhausting air from the furnace.

[0030] Open the ammonia valve to introduce ammonia gas at a flow rate of 5m³ / h. 3 / h, close the nitrogen valve, simultaneously open the natural gas and ignite the overflowing ammonia, allowing the workpiece to remain in the ammonia environment for 120 minutes, then close the ammonia valve and introduce nitrogen at a flow rate of 3m³ / h. 3 / h, turn off the heating element, turn off the natural gas when the furnace temperature drops to 450℃, and open the furnace cover to take out the sample when the furnace temperature drops below 100℃.

[0031] The nitriding layer microstructure and cross-sectional structure were observed using scanning electron microscopy. The cross-sectional structure of the nitriding layer obtained by the process of this invention is as follows: Figure 6 As shown, after ball milling with rare earth elements for 160 minutes, the sample surface showed many fine cracks, compared to... Figure 5 Compared to the nitrided layer after only room temperature ball milling, the nitrided layer is larger, indicating that the synergistic treatment of adsorbent materials and ball milling can make the workpiece nitrided more efficiently.

[0032] Example 2 This embodiment provides a method for improving the nitriding efficiency of steel by synergistically utilizing adsorbent materials and ball milling. The process flow is as follows: Figure 1 As shown, the specific process steps are as follows: (1) The quenching and tempering treatment of the matrix material is the same as in Example 1; (2) Polishing treatment: Same as in Example 1; (3) Ball milling treatment: 95% zirconia grinding balls (4mm in diameter), the polished workpiece, and the adsorbent material (Ti powder) were placed in a ball mill cylinder and milled for 220 minutes at room temperature. The mill cylinder speed was 160 r / min. The zirconia grinding balls occupied 1 / 3 to 1 / 2 of the mill cylinder volume, and the Ti powder was added at 1 / 10 of the mill cylinder volume. The workpiece was then removed, washed in water, wiped with alcohol, and dried. The resulting workpiece surface microstructure is shown below. Figure 3 As shown, after treatment with adsorbent material and ball milling, compared with the sample milled for 160 min, the surface of the workpiece has more protruding material and the sample surface is rougher.

[0033] (4) Nitriding treatment: Same as in Example 1.

[0034] The nitrided layer structure was observed using scanning electron microscopy. The nitrided layer structure obtained by the process of this invention is as follows: Figure 7 As shown, the nitrided layer thickness increases, but the surface still exhibits numerous voids and cracks. The nitrided layer thickness increases by approximately 0.15 mm compared to that obtained through conventional ball milling gas nitriding. Example

[0035] This embodiment provides a method for improving the nitriding efficiency of steel by synergistically utilizing adsorbent materials and ball milling. The process flow is as follows: Figure 1 As shown, the specific process steps are as follows: (1) Conditioning treatment of matrix material: Same as in Example 1.

[0036] (2) Polishing treatment: Same as in Example 1.

[0037] (3) Ball milling treatment: 95% zirconia grinding balls (4mm in diameter), the polished workpiece, and the adsorbent material (Ti powder) were placed together in a ball mill cylinder and milled for 280 minutes at room temperature. The ball mill cylinder speed was 160 r / min. The zirconia grinding balls occupied 1 / 3 to 1 / 2 of the mill cylinder volume, and the Ti powder was added to 1 / 10 of the mill cylinder volume. The workpiece was then removed, washed in water, wiped with alcohol, and dried. The resulting workpiece surface microstructure is shown below. Figure 4 As shown, after treatment with adsorbent materials and ball milling, the number and area of ​​protruding substances on the surface of the workpiece increased, and the surface roughness of the sample increased.

[0038] The particulate protrusions in the matrix material produced by the combined action of the adsorbent material and ball milling are shown in the SEM image. Figure 9 As can be seen, protrusions are formed on the substrate surface, which is a typical characteristic of friction. Electron microscopy was used to examine its composition.

[0039] Figure 10 The distribution diagram of Fe element shows that the surface protrusions are black, while other areas are red, indicating that the protrusions are not composed of Fe element. This demonstrates that using adsorbent materials in ball milling does not damage the matrix composition.

[0040] Figure 11 The protruding material is green, while the rest of the area is black, indicating that the protruding material is indeed the adsorbent material. This demonstrates that after the treated adsorbent material and the sample are ball-ground, the adsorbent material can be fixed in the matrix, which serves to protect the matrix and prepare for the next stage of nitriding.

[0041] (4) Nitriding treatment: Same as in Example 1.

[0042] The nitrided layer structure was observed using scanning electron microscopy. The nitrided layer structure obtained by the process in this embodiment is as follows: Figure 8 As shown, the nitrided layer is uniform and dense. The thickness of the nitrided layer is approximately 0.25 mm thicker than that obtained by conventional gas nitriding.

[0043] Comparative Example 1 The nitriding process used in Comparative Example 1 was: room temperature ball milling gas nitriding process. (1) Conditioning treatment of matrix material: Same as in Example 1.

[0044] (2) Polishing treatment: Same as in Example 1.

[0045] (3) Ball milling treatment: Place the 95% zirconia grinding balls with a diameter of 4mm and the polished workpiece into the ball milling cylinder. The zirconia grinding balls occupy 1 / 3 to 1 / 2 of the grinding cylinder. Ball mill for 280 minutes at room temperature. The ball milling cylinder speed is 160r / min. Then take out the sample, place it in water for cleaning, wipe it with alcohol and dry it.

[0046] (4) Nitriding treatment: Same as in Example 1.

[0047] The nitrided layer structure was observed using scanning electron microscopy. The nitrided layer structure obtained after ball milling is shown below. Figure 5 As shown, there is almost no nitriding layer, indicating poor nitriding effect.

[0048] Comparative Example 2 (1) Tempering of the base material: The workpiece is subjected to overall quenching followed by high-temperature tempering. The quenching temperature is 880℃, the quenching time is 150 min, the high-temperature tempering temperature is 800℃, and the tempering method is furnace cooling. The resulting workpiece surface microstructure is as follows: Figure 12 As shown in the figure. After analysis, when the quenching temperature is 880℃, the quenching temperature is too low. As can be seen from the figure, the structure is blocky and unevenly distributed, forming a mixed structure of sorbite and ferrite. The reason is that the quenching temperature is too low, resulting in a low degree of austenitization. Some structures in the steel do not have time to transform, and after tempering, the structure is easily enlarged due to the high temperature. The above-mentioned structure is formed for the above reasons.

[0049] (2) Polishing treatment: Same as in Example 1.

[0050] (3) Ball milling treatment: Place the 95% zirconium oxide grinding ball with a diameter of 4mm, the polished workpiece, and the adsorbent material (Ti powder) into the ball milling cylinder, and ball mill at room temperature for 280min. The ball milling cylinder speed is 160r / min. Then, take out the workpiece, wash it in water, wipe it with alcohol and dry it.

[0051] (4) Nitriding treatment: Same as in Example 1.

[0052] See Figure 13 After nitriding, the steel showed almost no nitrided structure, and numerous cracks appeared on the sample surface. Transverse fracture lines were observed in the lower and middle parts of the steel, and blocky fractures were observed in the center of the sample. This phenomenon is caused by the sample being heated at a low temperature, resulting in uneven austenite distribution and a blocky microstructure with weak inter-structure bonding. Therefore, after nitriding, nitrogen atoms penetrated into the gaps, widening them and exacerbating the cracking.

[0053] Comparative Example 3 (1) Tempering of the base material: The workpiece is subjected to overall quenching followed by high-temperature tempering. The quenching temperature is 1200℃, the quenching time is 150 min, the high-temperature tempering temperature is 800℃, and the tempering method is furnace cooling. The resulting workpiece surface microstructure is as follows: Figure 14 As shown, the microstructure consists of coarse martensite. Analysis revealed that when the quenching temperature was 1200℃, the excessively high temperature caused the austenite inside the steel to fully form and grow during the holding time, resulting in relatively coarse martensite during the cooling stage.

[0054] (2) Polishing treatment: Same as comparative example 2.

[0055] (3) Ball milling treatment: Same as comparative example 2.

[0056] (4) Nitriding treatment: Same as comparative example 2.

[0057] See Figure 15 The steel after nitriding has no nitrided structure and has good surface density without cracks. The reason for this phenomenon is that the structure (martensite) formed after quenching is relatively dense and has a high degree of bonding, resulting in high surface hardness. After ball milling, no small voids or cracks are formed on the surface of the steel, so the nitriding efficiency is poor and no nitrided layer is formed.

[0058] This invention discloses a method for improving the nitriding efficiency of steel through the synergistic effect of adsorbent materials and ball milling. The method includes matrix material preparation, addition of adsorbent materials, ball milling, and nitriding. The matrix material is prepared through a tempering process, and adsorbent materials are added in a ball mill. Through the synergistic effect of the adsorbent materials and ball milling, the adsorbent materials diffuse to the surface and subsurface layers of the matrix. Utilizing the strong affinity of the adsorbent materials for nitrogen, the diffusion rate of nitrogen into the matrix is ​​accelerated. Simultaneously, because ball milling creates defects at the grain boundaries on the surface of the steel matrix, nitrogen atoms can more easily penetrate into the matrix. The combined effect of these factors significantly improves nitriding efficiency, reduces production costs, and enhances enterprise production efficiency.

[0059] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.

Claims

1. A method for improving the nitriding efficiency of steel by synergistically utilizing adsorbent materials and ball milling, characterized in that, Includes the following steps: (1) Heat treatment of base material: The workpiece is subjected to overall quenching heat treatment and then high temperature tempering treatment. The quenching temperature is 950℃, the quenching time is 150min, the high temperature tempering temperature is 800℃, and the tempering method is furnace cooling. (2) Polishing treatment: After preliminary treatment with sandpaper of 150 grit, 400 grit, 1000 grit and 2000 grit respectively, the workpiece is polished to achieve a mirror effect. (3) Ball milling treatment: Place 95% zirconia grinding balls with a diameter of 4mm, the polished workpiece, and the adsorbent material into the ball milling cylinder. The adsorbent material is Ti powder. Ball mill for 280min at room temperature. The ball milling cylinder speed is 160r / min. The zirconia grinding balls occupy 1 / 3 to 1 / 2 of the ball milling cylinder volume, and the Ti powder addition amount accounts for 1 / 10 of the ball milling cylinder volume. Then, take out the workpiece, place it in water for cleaning, wipe it with alcohol and dry it. (4) Nitriding treatment: Place the ball-milled workpiece into the nitriding furnace, seal the furnace lid, start the heating element, raise the furnace temperature to 600℃, and after the temperature rise is complete, introduce nitrogen gas for 30 minutes, maintaining the furnace pressure at 1.3 atmospheres and the nitrogen flow rate at 5 m³ / min. 3 / h, exhausting air from the furnace; Open the ammonia valve to introduce ammonia gas at a flow rate of 5m³ / h. 3 / h, close the nitrogen valve, simultaneously open the natural gas and ignite the overflowing ammonia, allowing the workpiece to remain in the ammonia environment for 120 minutes, then close the ammonia valve and introduce nitrogen at a flow rate of 3m³ / h. 3 / h, turn off the heating element, turn off the natural gas when the furnace temperature drops to 450℃, and open the furnace cover to take out the sample when the furnace temperature drops below 100℃.

Citation Information

Patent Citations

  • Compressor blade and preparation technology thereof

    CN102410225A

  • Method for improving steel nitriding effect through high-temperature ball milling

    CN116590651A